2019
DOI: 10.1088/1361-6455/ab574f
|View full text |Cite
|
Sign up to set email alerts
|

Rotationally inelastic processes of C2− ( 2Σg+ ) colliding with He (1 S) at low temperatures: ab initio interaction potential, state changing rates and kinetic modelling

Abstract: We discuss in detail the quantum rotationally inelastic dynamics of an important anion often discussed as a possible constituent of the interstellar medium (ISM) and in different environments of circumstellar envelopes: the C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 56 publications
8
16
0
Order By: Relevance
“…The rate constants for C − 2 /p-H 2 (j = 0) calculated here and those for C − 2 /He which we have previously obtained in our earlier work [31] can be used now to check an approximation which is often employed in astrophysical modelling studies ( e.g. see: [64]), consisting in using the collisionally inelastic coefficients computed for the helium partner to further obtain those for H 2 as a partner by assuming the same value of their scattering crosssections.…”
Section: Rotationally Inelastic Scattering Cross-sections and Rate Constantssupporting
confidence: 75%
See 4 more Smart Citations
“…The rate constants for C − 2 /p-H 2 (j = 0) calculated here and those for C − 2 /He which we have previously obtained in our earlier work [31] can be used now to check an approximation which is often employed in astrophysical modelling studies ( e.g. see: [64]), consisting in using the collisionally inelastic coefficients computed for the helium partner to further obtain those for H 2 as a partner by assuming the same value of their scattering crosssections.…”
Section: Rotationally Inelastic Scattering Cross-sections and Rate Constantssupporting
confidence: 75%
“…In a series of recent works, we have investigated various inelastic processes of noble gas atoms colliding with C − 2 to assess their usefulness as buffer gases for cold-ion trapping experiments. Our simulations showed that thermalisation times of the rotational states of C − 2 with noble gases decreased in the order helium > neon > argon, due to the increasing interaction energy with atomic size and with dipole polarisability which are then yielding larger rate coefficients [31,32]. We have also calculated the rate coefficients for vibrationally inelastic collisional quenching of the anion's ν = 2 and ν = 1 levels [33], a step which can be useful in laser cooling experiments.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations

BASECOL2023 scientific content

Dubernet,
Boursier,
Denis-Alpizar
et al. 2024
A&A
Self Cite